Impact of efficacious and detrimental factors of social media on public usage behaviour in the age of covid-19 pandemic: in case of srikakulam, a.p. - Dr Koppala Venugopal,Dr Saumendra Das, Manoj Kumar Pukkala, Dr.Sabyaschi Dey (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Having attained the firm footing in technological adoption, the usage of social media sites by Indians have been found considerably significant. Yet, there has been the transition expected from certain demographical and geographical segments. Covid- 19 pandemic has become the driving force to the adoption of social media and the debate has been much on the extent of the impact explored efficaciously as well as detrimentally. Aiming to study the strength of the factors influencing the usage of social media by public, the research has been carried out to determine the extremity for both. Method mix of descriptive design, quantitative approach, convenience sampling technique and survey questionnaire are used for the research. Analysis of Multiple regression exhibited the strength of every element of variables influencing. Conclusions are made out of findings and interpretation to acknowledge the real status of usage pattern of social media by public during covid-19 situation.